The effect of magnetic marketing dimensions on company performance : applied research in the Iraqi General Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to test the effect between the independent variable, magnetic marketing across its dimensions (message, market, media) and the dependent variable, insurance company performance across its dimensions (financial performance, marketing performance). Accordingly, the research problem was defined by the main question: What effect can magnetic marketing have on performance? The Iraqi General Insurance Company was a place for the application, and the descriptive analytical approach was adopted. Accordingly, the questionnaire was prepared as a main tool in collecting data. The method of random sampling of (139) employees in the surveyed company was adopted, and the data was analyzed based on statistical programs (SPSS V). (28) (AMOS V.26) in calculating (the weighted mean, the standard deviation, the coefficient of variation, the Pearson correlation coefficient, and simple and multiple linear regression), and the research reached a set of results, including: There is a statistically significant effect for the dimensions of magnetic marketing (the message, Market, media) overall in the performance of the Iraqi General Insurance Company, as well as several recommendations, including: the need to focus the attention of the management of the Iraqi General Insurance Company on practicing and adopting magnetic marketing to enhance the company’s level of performance.